Continuous Heart Volume Monitoring by Fully Implantable Soft Strain Sensor. Issue 19 (6th September 2020) - Dual, Seraina A.; Llerena Zambrano, Byron; Sündermann, Simon; Cesarovic, Nikola; Kron, Mareike; Magkoutas, Konstantinos; Hengsteler, Julian; Falk, Volkmar; Starck, Christoph; Meboldt, Mirko; Vörös, János; Schmid Daners, Marianne
Abstract: Cardiothoracic open‐heart surgery has revolutionized the treatment of cardiovascular disease, the leading cause of death worldwide. After the surgery, hemodynamic and volume management can be complicated, for example in case of vasoplegia after endocarditis. Timely treatment is crucial for outcomes. Currently, treatment decisions are made based on heart volume, which needs to be measured manually by the clinician each time using ultrasound. Alternatively, implantable sensors offer a real‐time window into the dynamic function of our body. Here it is shown that a soft flexible sensor, made with biocompatible materials, implanted on the surface of the heart, can provide continuous information of the heart volume after surgery. The sensor works robustly for a period of two days on a tensile machine. The accuracy of measuring heart volume is improved compared to the clinical gold standard in vivo, with an error of 7.1 mL for the strain sensor versus impedance and 14.0 mL versus ultrasound. Implanting such a sensor would provide essential, continuous information on heart volume in the critical time following the surgery, allowing early identification of complications, facilitating treatment, and hence potentially improving patient outcome. Abstract : A soft flexible, strain sensor outperforms traditional clinical methods to measure left ventricular heart volume. The sensor can be directly applied to clinical settings in post heart surgery scenarios, and provide essential, continuous information on heart volume. Such technology would allow early identification of complications, using less personnel resources, facilitating treatment, and hence potentially improving patient outcome.